Reacciones adversas a medicamentos (ram) reportadas en el hospital iii essalud – chimbote durante el año 2008 - Cruz Bueza, Fredy Luis (2009)
Aim: To determine the characteristics of suspected adverse reactions reported by health personnel of the hospital III – Chimbote. Method: We performed a descriptive, cross-sectional, retrospective, framed in the field of Hospital Pharmacovigilance, were analyzed and classified all spontaneous reports of suspected RAM given to the Pharmacological Committee of Hospital III - Chimbote, from 1 january to 31 december of 2008. Results and Conclusions: There were 65 reports of suspected RAM with a total of 110 drugs involved. The most representative drug classes were: antihypertensives (43.6%), antibiotics (22.8%), NSAIDs (10.9%). The 41.5% of notifications were made by doctors, 48.5% for pharmaceutical chemist, in the type of RAM these were mostly of type B, with respect to severity, 45.5% were non-serious, the rate 37.3% 15.5% serious and severe type, and about 67.3% causality was probable, 21.8% possible and 7.3% of defined character